2007
DOI: 10.1002/ejoc.200601050
|View full text |Cite
|
Sign up to set email alerts
|

Procedures for and Possible Mechanisms of Pd‐Catalyzed Allylations of Primary and Secondary Amines with Allylic Alcohols

Abstract: This review describes the different Pd‐catalyzed methods that afford allylic amines from intermolecular reactions between allylic alcohols and amines and, with personal comments, the mechanisms that have been proposed. Allylic amines are an important class of compounds, while a wide structural variety of allylic alcohols are commercially available and are abundant in nature. The advantages of the use of allylic alcohols over that of their derivatives such as allylic esters or carbonates are the high atom effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(43 citation statements)
references
References 63 publications
0
43
0
Order By: Relevance
“…In principle, the nucleophilic attack could follow either an inner-sphere mechanism (first coordination of the nucleophile to the metal, followed by a reductive elimination step) or outer-sphere attack (direct attack of the nucleophile to the allyl moiety, without pre-coordination of the nucleophile to the metal). This strongly depends on the basicity of amines [26,27]. Strong nucleophiles (pKa > 20) are expected to attack the Pd metal and hence likely follow an inner-sphere mechanism while weaker nucleophiles (pKa < 20), such as N-methylaniline (pKa~10), are believed to attacked the allyl-moiety directly and likely follow an outer-sphere mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…In principle, the nucleophilic attack could follow either an inner-sphere mechanism (first coordination of the nucleophile to the metal, followed by a reductive elimination step) or outer-sphere attack (direct attack of the nucleophile to the allyl moiety, without pre-coordination of the nucleophile to the metal). This strongly depends on the basicity of amines [26,27]. Strong nucleophiles (pKa > 20) are expected to attack the Pd metal and hence likely follow an inner-sphere mechanism while weaker nucleophiles (pKa < 20), such as N-methylaniline (pKa~10), are believed to attacked the allyl-moiety directly and likely follow an outer-sphere mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, direct use of allyl alcohols as substrates was sought in order to make these CÀN coupling reactions much more attractive from an environmental and economical point of view. [6] Efficient catalysts featuring palladium [7][8][9][10][11][12][13][14][15][16] and iridium, [17,18] were devised but in most cases the presence of an activator (usually a Lewis acid) was still needed to facilitate departure of the OH group. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Two years ago, we reported on a complete mechanistic study of the allylation of primary amines catalyzed by palladium(0) complexes, [35] and we showed that the use of a significant amount of Lewis acid (at least in the case of palladium) is not a prerequisite provided that the ligands employed display a strong p-accepting capacity to facilitate the release of substrates from the intermediate 16-valence-electron(VE) complexes, and that traces (7), which was structurally characterized and appears to be a catalytic intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction proceeds under mild conditions of temperature both with primary and secondary amines. Furthermore, several stereoselective allylic substitutions including allylic amination have been reported using palladium catalysts [19][20][21][22][23][24]. Buono et al have shown that a Pd(0) asymmetric amination reaction on a prochiral substrate using various secondary amines proceeds as well in both the presence and the absence of an acceptor base [25].…”
Section: Introductionmentioning
confidence: 99%
“…Previously we have reported that the alkoxycarbonylation and the oxidative cleavage of allylic natural terpenic olefins, offers a very good method respectively for the preparation of new β,γ-unsaturated esters and ketoacids [28,29], which are of considerable value for the perfumery and pharmaceutical industry [30][31][32][33][34], as well as useful synthetic intermediates and chiral building blocks [35][36][37]. While the allylic amination in the presence of a palladium catalyst is known [24], its application to naturally occurring terpenes is interesting, because it serves as a tool for the synthesis of new enantiomerically pure amines. These deserve interest as ligands for transition metals presumably valuable for asymmetric catalysis.…”
Section: Introductionmentioning
confidence: 99%